China and Regional Security in South and Southeast Asia: A Comparative Analysis of ASEAN and SAARC - Bettani, Salman Ali; Ahmed, Zahid Shahab (JAS (Journal of ASEAN Studies), 2023)
Asian regionalism is largely represented by economic cooperation at sub-regional levels, and the Association of Southeast Asian Nations (ASEAN) is seen as a prominent example of that. In contrast, the South Asian Association for Regional Cooperation (SAARC) has failed to take off as a platform for economic cooperation and has been hostage to the India-Pakistan rivalry. While ASEAN was established as a forum to address members’ security apprehensions concerning China, SAARC was created to focus on regional cooperation in non-controversial matters like trade and human security. Hence, ASEAN has engaged more deeply with China through various mechanisms. Conversely, SAARC-China relations remain limited because India, the most dominant actor in the organization and the region, views China as a threat to its security and hegemony in South Asia. The research, therefore, aims to answer the following question: How does one region successfully manage security challenges/threats while the other remains ensnared by them? Resolving this puzzle necessitates a nuanced understanding of the role of regionalism in Southeast Asia, emphasizing the significance of comprehending the process and evolution of regionalism in this context. To address this inquiry, the research employs a comparative-historical analysis grounded in archival data encompassing both primary and secondary sources. The investigation reveals that SAARC’s limited engagement with China is a consequence of India’s opposition, a dynamic absent in ASEAN, where Indonesia actively supports cooperation with China. The research underscores the critical importance of unraveling the complexities of regionalism in Southeast Asia to grasp the underlying factors contributing to divergent outcomes in these regional organizations.